Tinjauan Yuridis Pertimbangan Hakim Dalam Menjatuhkan Sanksi Terhadap Pelaku Tindak Pidana Kelalaian Lalu Lintas yang Menyebabkan Hilangnya Nyawa Orang (Studi Kasusu No. 154/PID.B2015/PN.PW) - LA GURUSI (Jurnal Hukum Volkgeist, 2017)
High rates of traffic accidents (lakalantas) on its own if it is from a lack of public awareness in this respect motorists with a variety of factors. This type of research uses qualitative Analysis is the analysis of kualititif data against verbal and descriptive data are thought by describing the real circumstances from the object which will be discussed with formal and juridical approach refers to the concept of doctrinal law. Qualitative data are described by words or sentences split by category to derive the conclusion. The research results showed that the basic consideration of the judge in the criminal matter Number ruling dropped 154/Pid. B/2015/PN. Pasarwajo that is based on the fact the cause of the occurrence of the case i.e. belongs to a criminal act or omission with the evidentiary culpa at least two valid instrument of evidence, namely the description of witnesses, exhibits, letters of visum et repertum and description of the defendant. The advice of the author are the judges should be more sence to see the facts of what occurred at the time of the trial, therefore from the fact such arise, leading to the conviction of the judge that the accused may or may not are convicted and the judge must be more thorough and meticulous in disconnected matter, bearing in mind the letter ruling which is binding. It also must have knowledge or science of law well, is not only legal, but also a formal legal material in order not to wrong in dropping the verdict for a case.